Prevalence and Help Seeking Behavior for Non-Suicidal Self-Injury on College Students: 10.55131/jphd/2023/210219 - Hidayati, Farida; Fanani, Mohammad; Mulyani, Sri (Journal of Public Health and Development, 2023)
The high prevalence of NSSI has become a widespread health issue in various countries. Unfortunately, NSSI studies in Eastern countries are not as many as in Western countries. This study aims to explore the self-injury behavior of students in Indonesia. Crowdsourcing approach is used by distributing questionnaires through Google Form. A total of 909 students aged 18-25 years (mean age = 20.3, SD = 1,329, 75.4% female) participants completed the Inventory of Statements About Self-injury (ISAS) self-report scale to comprehensively assess non suicidal self-injury (NSSI). Participants were recruited during June 2022–July 2022. The results shows 30% of students were involved in NSSI behavior. The mean age of onset was 15.5 years. As many as 55% of subjects reported having committed more than 50 acts of self-injury. The reported NSSI methods included slashing (78% hair pulling, hitting 74%, biting 57.1%, interfering wound healing 46.9%, carving 26.7%, pinching 66%, scratching 63.3%, stabbing 25.2%, and ingesting a hazardous substance 7.3%. It was reported that 88.3% used more than one method, 17.2% did not feel pain while doing self-injury. In conclusion, the prevalence of NSSI among students in Indonesia is not different from other countries. Prevention and management actions need to be developed to help people who self-injure to have strategies in dealing with problems adaptively and avoiding risky behavior.